Decision Making Pattern Followed By Tribal Backyard Poultry Rearers In Bastar District Of Chhattisgarh - Chaturvedani, A.K.; Lal, Niranjan; Chander, Mahesh; Hussain, Khalid (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
This study assessed the decision making pattern of tribal backyard poultry production activities in Bastar district of Chhattisgarh. A multi-stage random sampling procedure was used to select 120 respondents (12 respondents per village) in the study. A structured interview schedule duly pre tested and validated was used to elicit information from the respondents. Data collected were analyzed using statistical tools like frequency counts and per centage. The results showed that average independent women participation was more in housing activities (67.50%), health care activities (57.29%) and feeding activities (53.89%) but participated less in breeding (39.17%), consumption (33.61%) and marketing (21.88%) activities.
Keywords: Tribal; decision making pattern; Backyard Poultry; Chhattisgarh